Crowding of international mutual funds - Artiga Gonzalez, Tanja; Dyakov, Teodor; Inhoffen, Justus; Wipplinger, Evert (Journal of Banking & Finance, 2024)
We study the relationship between crowding and performance in the active mutual fund industry. Using the equity holdings overlap of 17,364 global funds, we find that funds that crowd into the same stocks underperform passive benchmark funds by 1.4% per year. The negative returns to crowding can at least in part be explained by excess demand for liquidity and the associated discount for holding liquid stocks. We show that our measure of crowding contains novel information about performance that is not reflected in other variables that describe funds’ investment environment, such as fund size and style. Our findings suggest that crowding of investment opportunities is important for understanding diminishing returns.